LIBRARY INNOVATIONS IN THE DIGITALIZATION ERA: A SYSTEMATIC REVIEW - Maysa, Fuad; Latifah, Nor; Masruroh, Betty; Ningrum, Vira Setia; Laksana, Eko Pramudya; Anggoro, Bayu Koen; Djoumoi, Ahmed (Departemen Sastra Indonesia, Fakultas Sastra, Universitas Negeri Malang (UM), 2024)
This research presents a systematic review of trends and innovations in the library sector during the era of digitalization. As technology has advanced, libraries have transformed from traditional print-based service providers to dynamic digital platforms. This article explores several key aspects, including the nature of innovation in libraries, the challenges faced in implementing these innovations, their impacts, and recommendations for future practices. The study is based on a comprehensive analysis of literature sourced from Google Scholar, encompassing a review of 1,000 articles. The findings underscore the necessity of ongoing government support and the active involvement of community members in fostering successful innovation in libraries. Furthermore, this study offers valuable insights and recommendations for future research, emphasizing the critical role libraries play in promoting access to information and enhancing community engagement in a rapidly evolving digital landscape.